Towards new therapeutic strategies for cutaneous leishmaniasis - Cabral, Fernanda Viana (2021)
Cutaneous leishmaniasis (CL) is a zoonotic disease developed by protozoa parasites of genus Leishmania. It promotes destructive and ulcerated lesions with limited treatment options. There is an urgent need for the development of topical, cost-effective and efficacious treatments with minimized side effects to treat affected patients. The parasite-host interaction is of great importance since Leishmania parasites survive and replicate within host macrophages. As phagocytic cells, the activated macrophages produce reactive oxygen species (ROS) and nitric oxide (NO), which are toxic to pathogens, hence preventing parasites proliferation. However, Leishmania parasites can evade the host immune response and subvert antimicrobial macrophage defenses, thereby surviving within these cells even in harsh conditions. Indeed, the role played by ROS and NO in the control of CL has been under debate over the past years, emerging as potential alternatives to tackle this important neglected disease. In this regard, we aimed to evaluate the role of both NO and ROS towards antileishmanial activity using two different therapeutic strategies: (1) nitric oxide-releasing chitosan nanoparticles (NONPs) and (2) antimicrobial photodynamic therapy (PDT). For this, we focused on development and investigation of the potential of NONPs in vitro and in vivo against Leishmania amazonensis, one of the causative agents of CL. To assess the role of ROS, photodynamic therapy was investigated against different Leishmania species. Firstly, we evaluated the potential of organic light-emitting diodes (OLEDs) as a novel light source to inactivate in vitro promastigotes of L. major and L. amazonensis, using three phenothiazine dyes: Methylene blue, new methylene blue and 1,9-dimethyl methylene blue (DMMB). Then, we addressed the underlying mechanisms of DMMB-PDT upon promastigotes of L. amazonensis wild-type (WT) and miltefosineresistant (MFR) strains. DMMB-PDT effectiveness was also evaluated against intracellular amastigotes of WT and MFR together with cytotoxicity assay on mammalian cells. Our findings demonstrate that either NONPs or PDT are promising strategies to target CL and should be further explored for future preclinical and clinical trials.